(untitled) (Journal of Bangladesh Academy of Sciences, 2012)
Air particulate matter samples were collected using Air Metrics samplers from 11 - 17 January and 19 - 27 January, 2012 at Amin Bazar and Farm Gate sites, respectively. The sampling time was from 8 a.m. - 4 p.m. Three samplers were used of which two samplers were for PM2.5 samples, using Teflon and quartz filters and the others for PM10 samples using Teflon filter. Organic and elemental carbons (OC and EC) were measured in PM2.5 samples at both sites. It has been found that the EC concentration at Amin Bazar is higher than in Farm Gate. The contribution of EC may come from diesel, gasoline and coal/wood combustions in the Amin Bazar site. The present OC/EC data were compared with the previous data. It was found that the concentration of EC became higher than those in the previous year. During last couple of years, Government implemented different policies specially in case of motor vehicles to improve the air quality. But due to the use of diesel in quick rental power plants, the air quality start to deteriorate. BC plays an important role to change the climate. Hence, government should think of alternatives to meet the power demand in place of diesel. DOI: http://dx.doi.org/10.3329/jbas.v36i2.12970 Journal of Bangladesh Academy of Sciences, Vol. 36, No. 2, 241-250, 2012